Combining open and laparoscopic surgery for partial nephrectomy - Pahernik, Sascha; Reiter, Michael; Hatiboglu, Gencay; Huber, Johannes; Pfitzenmaier, Jesco; Haferkamp, Axel; Hohenfellner, Markus (Journal of endourology, 2011)
PURPOSE: We present a simple and easy to apply surgical approach for partial nephrectomy that combines open and laparoscopic surgery allowing for vascular control in technically challenging renal tumors and for reduction of ischemia time. - PATIENTS AND METHODS: Five patients underwent partial nephrectomy using the combined laparoscopic/open approach. After complete laparoscopic mobilization of the kidney and securing of the renal vessels, the kidney is transferred extracorporally through a small pararectal incision for tumor resection. - RESULTS: The technique was feasible in all cases, with no conversion needed. In three cases, no clamping of the renal artery was necessary. The mean operative time was 219 minutes (range 195-260 min). Pathologic examination revealed no malignancy in two (40%) cases. The estimated median blood loss was 500 mL (range 250-1000 mL). Renal function decreased from 84.9 mL/min (range 48.0-89.0 mL/min) to 78.8 mL/min (range 52.6-82.6 mL/min). Mean hospital stay was 5 days (range 3-14 d). - CONCLUSION: Based on our initial experience, we propose a feasible surgical option for minimally invasive partial nephrectomy, which is, in particular, suitable for technically challenging renal tumors (endophytic and central tumors, large tumors, tumors in solitary kidneys).
Gesehen am 06.09.2022